Oxo(corrolato)vanadium(iv) catalyzed epoxidation: oxo(peroxo)(corrolato)vanadium(v) is the true catalytic species. (15th February 2022) - Nayak, Panisha; Nayak, Manisha; Meena, Kiran; Kar, Sanjib
Abstract : Oxo(corrolato)vanadium(iv ) complexes are highly efficient oxidizers in the presence of H2 O2 and KHCO3, and oxo(peroxo)(corrolato)vanadium(v ) complexes are the catalytic intermediate. Abstract : de Visser et al. demonstrated theoretically that although vanadium(iv )-oxo complexes are slow oxidants, in the presence of H2 O2 they generated a side-on vanadium-peroxo complex, which is an efficient oxidizer. The catalytic activities of vanadium(iv )-oxo complexes are extensively reported in the literature in different ligand backbones, including porphyrin-based ligands. However, similar reports in corrole based ligand systems have not been explored to date. We have reported the synthesis and characterization of two new oxo(corrolato)vanadium(iv ) complexes. Interestingly, we have observed an anionic complex, [V IV O (Corr) 3− ] − . This data is contrary to what was observed earlier by Licoccia et al. We have observed that these newly synthesized oxo(corrolato)vanadium(iv ) complexes are highly efficient oxidizers in the presence of H2 O2 and KHCO3 . The catalytic reaction mixture was thoroughly analyzed, and it was established that an oxo(peroxo)(corrolato)vanadium(v ) complex is the true catalytic intermediate. This is the first report on oxo(corrolato)vanadium(iv ) complexes bearing meso -substitution. In addition to this, these oxo(corrolato)vanadium(iv ) complexes have never been previously investigated from a catalysis point of view.